Co-firing of blends of sugarcane bagasse and coal: Thermal and kinetic behaviors - Mortari, Daniela A.; Torquato, Lilian D. M. [UNESP]; Crespi, Marisa S. [UNESP]; Crnkovic, Paula M. (Springer Nature, 2018)
The interaction effects between sugarcane bagasse and a Brazilian coal during co-firing were investigated by means of thermal decomposition behavior, comparison between theoretical and experimental results, activation energy, and ignition temperature. The blends were prepared in the ratios of 100:0; 75:25; 50:50; 25:75; 0:100 (bagasse/coal). The interaction effect evaluated in this study was related to the interference of the bagasse volatile matter content in the coal thermal decomposition. The thermal decomposition behavior analyses were performed in a thermogravimetric balance, and the apparent activation energy was determined by two different models—model-free and local linear integral isoconversional method—under two different heating rate ranges. The results showed that the high volatile content of the sugarcane bagasse leads to more intense combustion, lower ignition temperature, and more complex reaction mechanism, as compared to coal. When the fuels are blended, there is a temperature anticipation of the events related to the decomposition of the coal portion in the mixture, the reaction rates increase and the ash formation is affected. The kinetic data also suggested that the interaction between both materials may occur and improve the burnout of the blend in relation to the pure coal firing due to the contribution of sugarcane bagasse volatile matter. Nevertheless, the presence of the bagasse did not allow to lower activation energy during the blends devolatilization process.
Keywords: Activation energy; Co-firing; Coal; Ignition temperature; Sugarcane bagasse; Thermal decomposition